Contextual-Based 3D Animation Video With Book Creator on Set Materials - Ummah, Diyah Nur; Ikashaum, Fertilia; Faniya, Venda Mega (Proceeding International Conference on Mathematics and Learning Research, 2023)
The research on the development of contextual-based 3D animation videos with a book creator is motivated by the use of school facilities such as projectors and computer laboratories that have not been used optimally. This study aims to produce a product in the form of a contextual-based 3D animation video with a book creator on the subject matter of the set. This type of research is research and development (R&D) with a 4D approach model. As for the quality of the product in terms of the aspects of validity, practicality, and effectiveness. The results of the study show that contextually based 3D animation videos with book creators achieve the validity criteria as seen from the validation results of material experts with a percentage of 91% achieving very valid criteria. The results of the media expert validation with a percentage of 80% reached the valid criteria, and the results of the post-test item content validation with a percentage of 72% reached the valid criteria. The results of the teacher response questionnaire with a percentage of 91% achieved very practical criteria and student response results with a percentage of 94% achieved very practical criteria. The results of the student's answer scores showed that there were 22 students who fulfilled the KKM with a percentage of 90.9% and 2 students did not fulfill the KKM with a percentage of 9.1%. The overall score is 1343 with a percentage of 87% indicating that contextually based 3D animation videos with book creators are effective. Based on the results of contextual-based 3D animation video research with a book creator that was developed to be valid, practical, and effective for use in learning mathematics.